EFEKTOKSISITAS BIJI KEMALAKIAN (Croton tiglium) TERHADAP MENCIT DAN ANJING - Yuningsih Yuningsih; Damayanti R (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Study in attempt to substitute commercial imported strychnine for elimination wild dogs in rabies disease program with Kimalakian (Croton tiglium) seeds has been conducted. This research was aimed to examine the destructive effect of croton seed petroleum extract (oil) in mice. There were 50 mice divided into 5 treatment groups. Each group was given (orally) 0.05, 0.10, 0.20, 0.40 and 0.80 ml oil/mice respectively and 1 group (10 mice) was blank. After the animal died necropsy was performed and gross pathological and hystopathological features were observed. The results showed that LD!0: 1.66 ml of oil/kg b.w. on mice. Furthermore, it was applied to dogs (b.w. 3kg) with dose: 2.5 ml, 5.0 ml and 10 ml oil/dog respectively. All dogs became hyperactive within few minutes, then dead after dosing 5.0 and 10.0 ml oil. Gross lesion in mices and dogs showed general congestion and hemorrhage in the lung, heart and liver. Histopathologically, the gastric mucosa was atropic resulted from gastric malfunction as leading to death.